Ammonium iodide-catalyzed radical-mediated tandem cyclization of aromatic aldehydes, arylamines and 1, 4-dioxane. (17th December 2021) - Liao, Yunfeng; Yan, Yiyan; Qi, Hongrui; Zhang, Weijie; Xie, Yanjun; Tao, Qiang; Deng, Jiyong; Yi, Bing
Abstract : We have developed a novel approach for the construction of 2-((2-arylquinolin-4-yl)oxy)ethan-1-ol derivatives involving a radical-mediated tandem cyclization reaction. Abstract : We have developed a novel approach for the construction of 2-((2-arylquinolin-4-yl)oxy)ethan-1-ol derivatives by an NH4 I-catalyzed radical-mediated tandem cyclization of three components including aromatic aldehydes, arylamines and 1, 4-dioxane. This strategy involves the breakage (C–H, N–H, CO, and C–O bonds) and formation (C–C, C–N and O–H bonds) of multiple types of bonds. This transformation could involve a radical-mediated tandem cyclization reaction instead of the typical [4+2] cycloaddition reaction of imines with olefins. 1, 4-Dioxane was used as a C4/O2 synthon to provide a 2-(vinyloxy)ethan-1-ol group.